Regime switches in the volatility and correlation of financial institutions - Kris Boudt; Jón Daníelsson; Siem Jan Koopman; Andre Lucas (National Bank of Belgium, 2012)
We propose a parsimonious regime switching model to characterize the dynamics in the volatilities and correlations of US deposit banks' stock returns over 1994-2011. A first innovative feature of the model is that the within-regime dynamics in the volatilities and correlation depend on the shape of the Student t innovations. Secondly, the across-regime dynamics in the transition probabilities of both volatilities and correlations are driven by macro-financial indicators such as the Saint Louis Financial Stability index, VIX or TED spread. We find strong evidence of time-variation in the regime switching probabilities and the within-regime volatility of most banks. The within-regime dynamics of the equicorrelation seem to be constant over the period.
Keywords: 330; Bank; Einlagengeschäft; Kapitaleinkommen; Volatilität; USA